Assessment of brain natriuretic peptide and copeptin as correlates of blood pressure in chronic hypertensive pregnant women - Chika J. Okwor; Kayode S. Adedapo; Oluwasomidoyin O. Bello; Ijeoma A. Meka; Chukwuemeka V. Okwor; Chukwuemelie Z. Uche; Chiebonam E. Nwajiobi; Uloaku A. Nto-Ezimah; Chisom E. Uchechukwu; Ekene J. Arum (BMC, 2022)
Abstract Background Hypertensive disorders of pregnancy including preexisting (or chronic) hypertension are the most common complication encountered during pregnancy that contribute significantly to maternal and perinatal morbidity and mortality. Brain natriuretic peptide (BNP) and copeptin have been investigated as biomarkers in various hypertensive disorders, but studies of their clinical value in chronic hypertensive pregnant women are sparce. This study aimed to assess the levels of BNP and copeptin in chronic hypertensive pregnant women and investigate their correlation with blood pressure (BP) in chronic hypertensive pregnant women in South Western Nigeria. Methods One hundred and sixty consenting pregnant women in their third trimester of pregnancy, grouped into those with chronic hypertension (n = 80) and normotensive (n = 80), were recruited for this cross-sectional study. Age and clinical characteristics were obtained, and blood was aseptically drawn for BNP and copeptin measurement using enzyme-linked immunosorbent assay. Data was analyzed with IBM SPSS ver. 20.0. Data was analyzed using Student t-test, chi-square, and Pearson correlation test as appropriate. Statistical significance was set at P < 0.05. Results The mean systolic BP (SBP) and diastolic BP (DBP) were significantly higher in pregnant women with chronic hypertension (158.30 ± 3.51 and 105.08 ± 2.47 mmHg, respectively) compared with normotensive pregnant women (100.72 ± 3.02 and 70.29 ± 1.96 mmHg, respectively). The mean levels of BNP and copeptin were higher in pregnant women with chronic hypertension (57.26 ± 3.65 pg/mL and 12.44 ± 1.02 pmol/L, respectively) compared with normotensive pregnant women (49.85 ± 2.44 pg/mL and 10.25 ± 1.50 pmol/L, respectively) though not statistically significant. Correlations observed between SBP and DBP with levels of BNP (r = 0.204, P = 0.200; r = 0.142, P = 0.478) and copeptin (r = − 0.058, P = 0.288; r = 0.045, P = 0.907) were not statistically significant. Conclusions There was no association between BP and the levels of BNP and copeptin in pregnant women with chronic hypertension who were already on antihypertensive treatment, with the implication that antihypertensive treatment may modulate BNP and copeptin release despite significantly elevated BP levels.